Relationships among the Internal Health Locus of Control, Mental Health Problems, and Subjective Well-Being of Adults in South Korea - Sunhwa Shin (MDPI AG, 2021)
The purpose of this study was to confirm the relationship between internal health locus of control, mental health problems, and subjective well-being in adults during the prolonged COVID-19 pandemic. In particular, the mediating effect of mental health problems on the relationship between internal health locus of control and subjective well-being was examined. A cross-sectional descriptive design was conducted via online survey. The participants were 600 adults over 20 years of age living in South Korea. The collected data were analyzed using hierarchical regression analysis and SPSS Process Macro (Model 4). As a result of the study, the internal health locus of control had a significant negative effect on mental health problems. In addition, in the process of the internal health locus of control affecting subjective well-being, the mediating effect of mental health problems was significantly shown. In the period of an infectious disease pandemic such as COVID-19, it is necessary to establish a strong internal health locus of control of individuals and to promote monitoring and treatment introduction for those with a low internal health locus of control. In addition, it was discussed that controlling mental health problems can improve subjective well-being, which is life satisfaction and happiness.